Retinitis pigmentosa-associated mutations in mouse Prpf8 cause misexpression of circRNAs and degeneration of cerebellar granule cells - Krausová, Michaela; Kreplová, Michaela; Banik, Poulami; Cvačková, Zuzana; Kubovčiak, Jan; Modrák, Martin; Zudová, Dagmar; Lindovský, Jiří; Kubik-Zahorodna, Agnieszka; Pálková, Marcela; Kolář, Michal; Procházka, Jan; et al. (Life science alliance, 2023)
A subset of patients with retinitis pigmentosa (RP) carry mutations in several spliceosomal components including the PRPF8 protein. Here, we established two alleles of murine Prpf8 that genocopy or mimic aberrant PRPF8 found in RP patients-the substitution p.Tyr2334Asn and an extended protein variant p.Glu2331ValfsX15. Homozygous mice expressing the aberrant Prpf8 variants developed within the first 2 mo progressive atrophy of the cerebellum because of extensive granule cell loss, whereas other cerebellar cells remained unaffected. We further show that a subset of circRNAs were deregulated in the cerebellum of both Prpf8-RP mouse strains. To identify potential risk factors that sensitize the cerebellum for Prpf8 mutations, we monitored the expression of several splicing proteins during the first 8 wk. We observed down-regulation of all selected splicing proteins in the WT cerebellum, which coincided with neurodegeneration onset. The decrease in splicing protein expression was further pronounced in mouse strains expressing mutated Prpf8. Collectively, we propose a model where physiological reduction in spliceosomal components during postnatal tissue maturation sensitizes cells to the expression of aberrant Prpf8 and the subsequent deregulation of circRNAs triggers neuronal death.
Keywords: Cerebellum; myši; RNA, Circular; mozeček; proteiny vázající RNA; Mutation; mutace; Animals; Mice; RNA-Binding Proteins; Retinitis Pigmentosa; zvířata; kruhová RNA; retinopathia pigmentosa